Outcomes in Pregnancies With a Confined Placental Mosaicism and Implications for Prenatal Screening Using Cell-Free DNA. Issue 7 (July 2020) - Grati, Francesca Romana; Ferreira, Jose; Benn, Peter; Izzi, Claudia; Verdi, Federica; Vercellotti, Elena; Dalpiaz, Cristina; D'Ajello, Patrizia; Filippi, Elisa; Volpe, Nicola; Malvestiti, Francesca; Maggi, Federico; et al.
Abstract : (Abstracted from Genet Med 2020;22:309–316) The most common type of confined placental mosaicism (CPM), the presence of a chromosomal abnormality in the placenta but not in the fetus, involves trisomy/disomy. Confined placental mosaicism occurs in 97% of rare autosomal trisomy (RAT) cases detected by chorionic villus sampling (CVS).